Isolation and Characterization of Cellulose from Sugar Palm Pulp Using the Alkaline Method - Yelmira Zalfiatri; Rahmayuni Rahmayuni; Rahmadini Payla Juarsa; Yanti Nopiani; Ahmad Ibrahim Roni Surya Hasibuan; Dinda Yusra Danil; Siti Nuraisah (Green Engineering Society, 2026)
Sugar palm pulp is a by-product generated during the palm starch filtration process and contains lignocellulosic components. These lignocellulosic components can be separated through a delignification process. One chemical method of delignification uses an alkaline solvent. This study aimed to determine the optimal concentration of sodium hydroxide (NaOH) for maximising cellulose yield from sugar palm pulp and to characterise the resulting cellulose. The research was conducted using a completely randomised design (CRD) with four treatments and four replications. The treatments consisted of varying NaOH concentrations: K1 (1% w/v), K2 (3% w/v), K3 (5% w/v), and K4 (7% w/v). Observations were made on yield, moisture content, ash content, pH, colour, and iodine test. Data were analysed using analysis of variance (ANOVA). If the calculated F-value was greater than or equal to the tabulated F-value, the treatment effect was considered significant, and the analysis proceeded with Duncan's multiple range test at the 5% significance level. The results showed that sodium hydroxide concentration significantly affected yield, moisture content, ash content, pH, and colour. The selected treatments (3% NaOH concentration) yielded cellulose with the following characteristics: yield of 34.07%, moisture content of 6.8%, ash content of 5.99%, pH of 8.68, and whiteness degree of 36.65%. The colour coordinates were L=37.27 (low brightness) a=0.62 (slight redness) b=1.74 (slight yellowness). The iodine test resulted in a brown colour, indicating a positive reaction for cellulose.